Low Dose Lipopolysaccharide-Induced Depressive-Like Phenotype is Mediated by Proinflammatory Cytokines in Mice and Role of Ketamine - Praharaj, Shuvranshu; Kalaichelvan, Vandurayanpet Kaliyamoorthy; Murugan, Vedigounder; Venkatachalam, Velappan; Ahmad, Ishtiyaque (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Depression is a common mental illness, with an estimated 3.8% of global population affected. In the pathophysiology of depression, ketamine acts quickly in patients. Treatment with low-dose ketamine upon administration to stressed C57BL/6J mice is now a major translational research area to facilitate further innovation. Objectives The present work was aimed to establish a depressant like animal model after 6 days of LPS injection, where LPS did not promote body weight loss. Materials and Methods Peripheral administration of low dose of Lipopolysaccharide (LPS) activates cytokines and culminate in a distinct depressive-like behavioral syndrome, measured by increased duration of immobility in the forced swim and anhedonia in sucrose preference tests. Cytokines like TNF-α, IL-6, IL-1β and IFN-γ were determined in brain homogenate and in plasma using western blot performed with automated Jess system (ProteinSimple) and ELISA respectively. Results Ketamine prevents development of depressive-like behavior by decreasing swimming behavior and increasing preference to sucrose in stressed animals. Ketamine treatment reduced the LPS induced secretion of IFN-γ (p <0.05 for 30 mpk), IL-6 (p <0.05 for 30 mpk), TNF-α (p <0.0001 for 30 mpk) and IL-1β in plasma. Similarly, ketamine treatment reduced the LPS induced secretion of IFN-γ (p <0.001 for 10 and 30 mpk), IL-6, TNF-α (p <0.01 for 10 and 30 mpk) and IL-1β (p <0.05 for 10 mpk, p <0.0001 for 30 mpk) in brain. The plasma and brain concentrations of ketamine were analysed using LC-MS/MS and Brain/ Plasma ratio (B/P) of ketamine at 10 and 30 mpk were calculated as 0.70 and 0.82 respectively. Conclusion In summary, these data emphasizes that ketamine treatment modulate cytokine level, showed good brain to plasma exposure and provides its anti-stress effects in the C57BL/6 mouse strain, which may be possible reason for the anti-depression property and is relevant to human stress-induced depression.
Keywords: B/P; Cytokines; Depression; LPS; FST; SPT